(untitled) (Revista de História da UEG (REVHIST), 2023)
The slave quarters, at times in the history of Brazil, was the reason for many headaches for those who lived in the big house. In this article, we investigate one of these moments, specifically the uprising of slaves on the property of Colonel José Henriques Flores, which took place in the village of Itajahy, province of Santa Catarina, in the year 1867. Based on interviews, memories and newspaper articles, at first, we try to reconstruct the controversial figure of this master of slaves. Then, through the judicial process brought about by this uprising, we analyze the organization of the enslaved people involved, as well as their demands for better working conditions and survival. Keywords: Rebellion. Enslaved. Africans. Creoles. Mistreatment.